The effect of body mass index (BMI) on the performance in prayer by Muslims : preliminary report of the study on range of motion of the hip and knee - Sharifudin, Mohd Ariff; Arshad, Ahmad Afiq; Johari, Muhammad Hafiz; Rahimin Affandi, Muhammad Ali Sajjad; Taib, Mai Nurul Ashikin; Che Mohamad, Che Anuar; Roslan, Rosazra; Ab. Rahman, Norhafiza (2014)
Background and Objectives: Praying or solah, represent a paramount and fundamental activity of daily living in Muslim community. Muslims need to adopt several postures that require deep flexion of the knee and hip to perform this daily obligation. The intention of this study is to simultaneously obtain normative passive and functional range of flexion data during Muslim prayers in the knee and hip joints of normal Muslim adults. Methodology: A cohort of Malay men aged between 20 to 30 years was recruited in this cross-sectional study. Passive range of motion and flexion angles of the hip and knee joints in various postures during prayer were measured using a standard goniometer. The difference against existing normative range of motion database available and the influence of various factors formed the core matter of this study. Factors analyzed include body mass index (BMI), length of limbs, abdominal and limb circumferences. Results: 60 participants were recruited for the preliminary phase of this study. The mean (SD) of the passive hip flexion and passive knee flexion were higher compared to other existing normative range of motion database. The BMI demonstrated a significant correlation with the passive range of motion of the knee joint but not statistically proven with the hip joint. The hip and knee flexion arc in this study were from 74.1° to 119.0° and from 3.3° to 119.7° respectively for the young Malay male adults performing prayers. Conclusion: The ROM involved for prayers was more for the knee joint and less for the hip joint as compared to the measured passive ROM. This reflects that a higher knee flexion angle compared to hip flexion is necessary to attain the sitting postures. BMI has a significant linear negative relationship with the knee passive ROM. A unit increase in BMI will have 0.782 units lower of ROM of the knee joint.